Beyond the Classroom: A Comparative Study of Subjective Well-Being Among Early Childhood Teachers in Indonesia and Malaysia - Teguh Fachmi; Seah Siok Peh; Rohman (Jurnal Iqra': Kajian Ilmu Pendidikan)
This study explores the differences in Subjective Well-Being (SWB) among early childhood education (ECE) teachers in Indonesia and Malaysia. A total of 200 teacher of ECE participated. Statistical tests indicated that the data from both groups significantly deviated from a normal distribution. As a result, the non-parametric Mann-Whitney U test was applied to compare the SWB scores, revealing a significant difference between the two countries (p = 0.015). Teachers in Malaysia reported higher SWB, suggesting that cultural and educational policies may influence well-being. Regression analysis assessed the impact of work tenure and gender on SWB, but neither factor was found to be significant. Notably, years of service negatively affected SWB, indicating that longer tenure is associated with lower well-being in both countries. These results highlight the importance of considering contextual factors such as social support and work-life balance in addressing teacher well-being. This study addresses a significant research gap by providing cross-national evidence on subjective well-being (SWB) among early childhood education (ECE) teachers in Southeast Asia, this research offers novel insights into how national education systems and socio-cultural environments influence teacher well-being. By comparing Indonesia and Malaysia, the study highlights previously unexplored regional differences and underscores the need for context-sensitive policy interventions across diverse educational settings.